Penerapan Sistem Pendukung Keputusan Untuk Memprediksi Kinerja Supplier Terbaik Menggunakan Metode Naive Bayes (Studi PT. Shin Heung Indonesia) - Muhammad Makmun Effendi; Ermanto Ermanto; Moh Khamim (Jurnal SIGMA, 2022)
In companies usually always assessing suppliers but in this company it's still subjective so that in this research, aims to predict suppliers best by implementing decision support system for get the best supplier predictions objective with naive bayes method using assessment parameters quality, capacity, price, service and this parameter to get the criteria best supplier status, good supplier and suppliers are not good. In this research made a test data with value criteria quality, capacity, price, service by generating a prediction the best supplier status because it has the highest value with a value of 1, while for suppliers both 0.6 and suppliers unfavorable is 0.1. Support system the decision to predict the best supplier using naive algorithm method Bayes can make it easier to get best supplier predictions. Keywords: Sistem Pendukung keputusan, Php, NaÃ¯ve Bayes